Keanekaragaman Semut (Hymenoptera: Formicidae) di Beberapa Tegakan di Taman Hutan Raya Sultan Thaha Syaifuddin Jambi - Noor Farikhah Haneda; Ajeng Dwi Larasati (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Biodiversity can act as an indicator of the ecological system and as a medium for knowing species changes. Insects are living things in a world that has a high species diversity. One insect that has a functional role in the ecosystem is ants. The purpose of this study was to calculate and analyze diversity of the types of ants in four types of ecosystems and analyze the effect of habitat characteristics on the abundance of ants. Ant sampling using the hand sorting method was taken from the soil and litter parts in four ecosystems, namely secondary forest, ulin stands, oil palm plantations, and rubber stands in Sultan Thaha Syaifuddin Forest Park Batanghari District, Jambi Province. The results showed a total of 940 ants were obtained, from 296 individuals in Secondary Forest, 198 individuals in oil palm plantations, 307 individuals in ulin stand, 139 individuals in rubber stand. Ants are more commonly found in parts of the soil than litter. The highest ant diversity in the soil and litter is found in secondary forest. Environmental factors that influence the presence of ants in each ecosystem are soil temperature and thickness of litter. Keywords: ants, biodiversity, ecosystems, hand sorting, tahura.